Design of robotic mannequin formed by flexible belt net. (May 2019) - Li, Jituo; Weng, Jiawei; Xu, Haocan; Zhou, Chengdi; Zhang, Dongliang; Lu, Guodong
Abstract: A robotic mannequin is a shape-changing robot that can simulate human body shapes. Inspired by the three-dimensional parametric human modeling technology, a novel robotic mannequin structure, the flexible-belt-net-based robotic mannequin, has been proposed in this paper. Devices have been designed to enable a tensioned flexible belt to elongate, shorten, and bend as a mathematical curve. The shape of the tensioned flexible belt is determined by the elastic bars it envelopes. Each elastic bar is statistically designed on the basis of a large number of scanned human models. When the flexible belt is tensioned, it forces the elastic bars to bend and adjust their postures adaptively, shaping the flexible belt. This study is the first to design and control a robotic mannequin with flexible belts, bridging the virtual parametric human model to physical shape-changing mannequin. A flexible-belt-net-based robotic mannequin that can simulate medium-sized human bodies has been prototyped to evaluate our approach. Highlights: Simulating various human bodies by flexible-belt-net with its topology being a quadric mesh. Bridging the physical robotic mannequin and virtual curves controlled parametric human model. Designed devices to make the lengths and shapes of flexible belts changeable and controllable.